Per Vaginal Delivery Following Partial Fetotomy In Fawn With Bilateral Shoulder Flexion - Kumar, S.; Pandey, A. K.; Saini, G.; Saini, P.; Ravish , S. (The Indian Journal of Animal Reproduction, 2021)
Present case reports depicted successful management of dystocia due bilateral  shoulder flexion in a free ranging deer. Deer was presented with head of fetus  occuluding the birth canal. Clinical examination revealed bilateral shoulder  flexion and dystocia was successfully managed through partial fetotomy of head  and subsequent obstetrical mutation.
Keywords: Bilateral shoulder flexion; Deer; Dystocia; Fetotomy; Local Anaesthesia